Experiences from the United Kingdom in the regulation of privatised utilities - Kay, John (Statistical and Social Inquiry Society of Ireland, 2000)
As Ireland embarks on a programme of privatisation and liberalisation of markets, it may be informative to reflect on the experiences of the UK on competition, privatisation and regulatory issues in the utilities sector over the last two decades. The regulation of privatised utilities in Britain is widely criticised today. The criticism comes from many quarters. Customers resent their money being handed out in excessive salaries and dividends. Academics are now widely critical of the RPI-x formula for capping prices below the retail price index (RPI), which was once a proud British innovation. A curious alliance of politicians and senior industry executives is concerned to suggest that the regulatory process is insufficiently accountable.
Symposium on market liberalisation in Ireland: competition, privatisation and regulatory issues
Read before the Society, 20 January 2000
Keywords: Market liberalisation; Privatisation; Government regulation; Utilities; Competition policy; 314.15